1980
DOI: 10.2307/1942656
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore‐Plant Interactions of Individual Limpets Maintaining a Mixed Diet of Intertidal Marine Algae

Abstract: Plate limpets, Acmaea (Notoacmea) scutum, are common in central California on mid—intertidal vertical faces, where they ignore erect algae and consume primarily two encrusting algae, Petrocelis middendorffii (=P. franciscana) and Hildenbrandia occidentalis. This mid—intertidal system offers a manageable diversity of species, slow—moving consumers, and a two—dimensional, stationary food resource. Such an assemblage of organisms enables detailed studies on food selection within localized sets of available foods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…Because we held the total amount of algae offered to each herbivore constant, the amount of each algal species consumed was less in mixture than in the corresponding single species diet treatments (the most preferred species composed, at most, 50% of diet in mixtures). As a result, the greater performance of herbivores on mixed diets was not solely the result of including a single high-quality food, but was instead likely due to complementarity among algal species in nutritional benefit or dilution of algal chemical or morphological features that negatively impact herbivore fitness (Kitting 1980, Pennings et al 1993, CruzRivera & Hay 2003. Crabs preferred and had the highest growth on Cladophora columbiana and Ulva sp.. Because 72% of the total consumption in mixed diet treatments was of these 2 species, the mixing of these 2 species may be important for crabs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we held the total amount of algae offered to each herbivore constant, the amount of each algal species consumed was less in mixture than in the corresponding single species diet treatments (the most preferred species composed, at most, 50% of diet in mixtures). As a result, the greater performance of herbivores on mixed diets was not solely the result of including a single high-quality food, but was instead likely due to complementarity among algal species in nutritional benefit or dilution of algal chemical or morphological features that negatively impact herbivore fitness (Kitting 1980, Pennings et al 1993, CruzRivera & Hay 2003. Crabs preferred and had the highest growth on Cladophora columbiana and Ulva sp.. Because 72% of the total consumption in mixed diet treatments was of these 2 species, the mixing of these 2 species may be important for crabs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, herbivore-deterrent chemistry or morphology that can reduce performance in some herbivore species, such as phenolics in Pelvetiopsis limitata and dimethylsulfoniopropionate in Ulva spp. (Kitting 1980, Steinberg 1985, Van Alstyne et al 1999, 2009), could be less harmful when diluted in mixed diets. Our experiments did not explicitly test for the mechanisms underlying this complementarity, but we will discuss possible characteristics of the algae that might underlie this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported that encrusting algae rely on the presence of herbivores to prevent overgrowth by erect forms (Kitting 1980, Paine 1980, Steneck 1982. Others (Bertness et al 1983, Sebens 1983, Masaki et al 1984, Johnson & Mann 1986, Dethier 1994 and references therein) have shown that crusts were able to reduce settlement of potential competitors, suggesting that their persistence does not strictly depend on the control of erect species by grazers.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the dominant species, their feeding habits and mechanisms of adaptions to environmental factors, four types of biological interactions may influence the community patterns: (1) P r e d a t i o n (see Connell, 1970, I975;Dayton, 1971Dayton, , 1975Paine, 1974Paine, , 1976Menge, 1976Menge, , 1978aMenge, , 1978bMenge, , 1983Menge & Sutherland, 1976Connell & Slatyer, 1977;Lubchenco & Menge, 1978;Hughes, 1985;Marsh, 1986;Petraitis, 1987). (2} H e r b i v o r y (sometimes also called "grazing", though this means something different to a lotof scientists: see Paine & Vadas, 1969;Dayton, 1971Dayton, , 1975Connell & Slatyer, 1977;Lubchenco, 1978Lubchenco, , 1980Lubchenco, , 1982Lubchenco, , 1983Lubchenco & Menge, 1978;Kitting, 1980;Lein, 1980;Lubchenco & Cubit, 1980;Underwood, 1980Underwood, , 1984aUnderwood, , 1984bLubchenco & Gaines, 1981;Robles & Cubit, 1981;Underwood & Jernakoff, 1981;Gaines & Lubchenco, 1982;Steneck, 1982;Bertness et al, 1983;Hawkins & Hartnoll, 1983;Cubit, 1984;Hartnoll & Hawkins, 1985;Jernakoff, 1985a…”
Section: Introductionmentioning
confidence: 99%